The Effects of Foot Reflexology Massage on the Sleep Quality of Nurses Working in the Selected Hospitals of Sabzevar University of Medical Sciences - Mojgan Gholitabar Omrani; mohammad Reza Ghasemi; Mohammad Gholizadeh Gerdrodbari; Roghayeh Javan; Neda Mahdavifar (Traditional and Integrative Medicine)
Poor sleep quality has always caused problems for nurses in providing healthcare. Today, foot reflexology massage is considered adjunctive therapy in improving sleep quality. Therefore, this study aimed to evaluate the effects of foot reflexology massage on the sleep quality of nurses. This controlled clinical trial was conducted on 80 nurses working in the selected hospitals of Sabzevar University of Medical Sciences. The nurses meeting the inclusion criteria were selected using the available sampling method and divided into two intervention and control groups, each containing 40 subjects using the permuted block technique. In the intervention group, foot reflexology massage was conducted by each research unit for 12 sessions, each for 30 minutes for six weeks. Both groups performed the Pittsburgh sleep quality index at the beginning of the study and five days after the intervention. Data were analyzed using SPSS 24 using descriptive and deductive tests. The mean sleep score in the control and intervention groups was 9.22±3.30 and 9.90±3.47, which was 9.05±3.35 and 6.97±2.68 after the intervention, indicating a significant difference in reducing the overall score of the intervention group compared to the control (p=0.000). Moreover, decreased sleep quality, sleep latency, sleep efficiency, and sleep duration scores were significant after the intervention (p<0.05). Based on the results, foot reflexology massage can enhance nurses' sleep quality. Therefore, nurses are advised to utilize it as a valuable and practical approach to improve their sleep quality.